2020
DOI: 10.1016/j.fuel.2020.118744
|View full text |Cite
|
Sign up to set email alerts
|

Parametric investigation of pre-injection on the combustion, knocking and emissions behaviour of a large marine four-stroke dual-fuel engine

Abstract: This study aims at the parametric investigation of a large marine four-stroke dual-fuel engine in order to identify the pre-injection effects on the engine combustion, knocking and emissions parameters.A model was employed that was developed by integrating a 1-D engine model in AVL-BOOST and a 3-D CFD model in CONVERGE. The MAN 51/60DF marine engine is modelled and the simulation results were validated against experimental data. Subsequently, parametric runs for various pre-injection timings and mass ratios ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…More recently, in Wang et al (2020) the authors performed a parametric investigation of a large four-stoke dual-fuel marine engine in order to identify the pre-injection effects on the engine combustion, knocking and emissions parameters. Their modelling approach consisted of the integration of a 1-D model and a 3-D computational fluid dynamics (CFD) model utilising the MAN 51/60DF marine engine as a case study.…”
Section: Pmsmentioning
confidence: 99%
“…More recently, in Wang et al (2020) the authors performed a parametric investigation of a large four-stoke dual-fuel marine engine in order to identify the pre-injection effects on the engine combustion, knocking and emissions parameters. Their modelling approach consisted of the integration of a 1-D model and a 3-D computational fluid dynamics (CFD) model utilising the MAN 51/60DF marine engine as a case study.…”
Section: Pmsmentioning
confidence: 99%
“…Such data were not available. Other approaches reported in the pertinent literature include the combination of 0D/1D and 3D CFD modelling for the combustion [14,68]. However, such more detailed combustion modelling approaches are associated with a considerable computational effort, and therefore are not recommend for optimisation studies that include a large number of simulation runs, which was the case in this study.…”
Section: Combustion Modellingmentioning
confidence: 99%
“…In [107] the authors used a combination of coherent flame and surface wrinkling model and declared that in spite of capturing some physical trends, further improvements of the mixing controlled combustion are still needed. Research work was carried out with a special focus on the extended chemistry involved due to the two fuels in [108][109][110]. Eder et al showed results with an ECFM-3Z model and empiric correlations for ignition delay and laminar flame speed [111] that reasonably correlated with test data.…”
Section: Flame Propagationmentioning
confidence: 99%